Compatibility of a Mixture of Carica Papaya Leaf Exract and Ageratum Conyzoides Against Leptocorisa Oratorium F. in Rice Plants - fitri, Silvia; Mawardi; Syarief, Mochamad (JURNAL AGRIMENT, 2024)
This research was carried out at the Jember State Polytechnic Plant Protection Laboratory, field tests in Dukuh Mencek Village, Sukorambi District, Jember Regency, Indonesia from June-September 2021. Comparing population and intensity attacks of L. oratorius, diversity of arthropod species (herbivores, predators, and pollinators), Shannon Wiener index (H'), Simpson Dominance Index (C'), Sorensen Similarity Index (SSI) and crop yields between the  Cp+Ac  and Alfametrin (Am). The aim were to study the compatibility of a mixture of C. papaya and A.conyzoides leaf extract (Cp+Ac); Against L. oratorius F. and beneficial arthropods. The. Arthropod collection using sweep net, Yellow pan trap, Sticky Trap. The results of the research were the Cp+Ac Compatibility Index = 0.4 (strong synergy), population and  the intensity attack were not significantly different, The Cp + Ac treatment found 9 orders, 14 families, 15 species, Am: 9 orders, 13 families, 13 species. The number of herbivores individual were not significantly different, predator and pollinators Cp + Ac was greater than Am. H', both treatments were in the medium category, ecosystem was balanced, both species do not have dominance, the SSI were similar. Grain dry weight of Cp+Ac was 48.10 g per clump, heavier than Am, was 42.26 g per clump. Keywords: A. conyzoides leaves extract , beneficial arthropods, compatibility index; C. papaya